Conceptual Fundamentals of digital transformation of economy - V. M. Mineeva (Путеводитель предпринимателя, 2020)
Today, the digital economy determines that market leaders determine not a long-term success story, not the value of real estate and assets, not the number of patents or access to capital, but the ability to change and adapt their business to new conditions.